Effectiveness of New-Normal Health Services of the Health Professional Network in Sawi District, Chumphon Province - สมตน, อัญญารัตน์; คงศีล, สุคนธา; เจียมตน, สุขุม; สัตยสมบูรณ์, ยุวนุช; พงศ์พิรุฬห์, กฤษณ์ (Journal of Health Science of Thailand, 2023)
This analytical cross-sectional study aimed to identify the relationship between personal characteristics, transformational leadership, motivation, and the effectiveness of new-normal health service delivery of the health professional network in Sawi District, Chumphon Province. Study samples were 204 medical or health personnel. The research instrument consisted of self-administered questionnaires on transformational leadership, job motivation factors, and opinions on the effectiveness of the new-normal health service delivery. The data were collected and analyzed using descriptive statistics and the Chi-Squared test. The results showed that the effectiveness of new-normal health service delivery of the health professional network in Sawi District, Chumphon Province was at a high level (M=3.61, SD=0.45). Three factors found to be significantly associated with the effectiveness of new-normal health service delivery of the health professional network in Sawi District were educational level, transformational leadership, and job motivation (p<0.05). The effectiveness of the new normal health service delivery increased when the personnel had more motivation to provide the service and recognize that leaders have more transformational leadership. The results could be applied in strategic planning and the development of a health management system by making an integrated plan. Pay attention to the qualities of the leader for increasing the effectiveness of new-normal health service delivery are proposed. Regular reviews and supporting plans to deal with the unwanted incidence in service delivery should be established. This would build the confidence and readiness of health professionals in responding to emerging diseases. Priority should be given to the use of innovation, medical literacy promotion, and human resource management for the health professional network to better deliver new-normal health services.